Penerapan Inventory Control untuk Meningkatkan Cost Efficiency pada Perusahaan Distributor PT. Y - Nicholas Billy; Yulia Yulia; Rudy Adipranata (Jurnal Infra, 2022)
PT. Y is a distributor company that sells water heaters and several water heater accessories. The problem is that all sales and stock bookkeeping is still done manually via excel separately - excel data is separated so that there are often missing excel. The stock check process is also done manually by counting the items one by one within a certain time so that it takes a long time. Too much stock because they also want to buy items at low prices is also a problem. From the existing problems, PT. Y requires an administrative system that helps summarize sales and purchase data as well as methods in the form of Economic Order Quantity and Reorder Points to help PT. Y in preparing stock so as not to buy too much stock With the Inventory Control System that will be applied to PT. Y will help with the problem of miscalculation of excel data. Better stock management and purchase of goods with good calculations will help cost efficiency at PT. Y